Improving the implementation of KiVa antibullying program with tailored support: Study protocol for a cluster randomized controlled trial - Herkama, Sanna (Elsevier, 2025)
Background
There are no evidence-based models to support the implementation of school-based bullying prevention programs. Our primary objective is to examine the impact of tailored support on the implementation of the KiVa antibullying program. Our second objective is to evaluate whether the offered support influences student outcomes (e.g., victimization, bullying perpetration). We also assess the cost-effectiveness of the provided support and conduct a process evaluation.
Methods
In a cluster randomized control trial (cRCT), we compare program fidelity between schools that receive implementation support and those that do not. Twenty-four (N = 24) schools in Finland were randomized to either the IMPRES condition (receiving support, n = 12) or the control group (KiVa as usual, n = 12). In the IMPRES condition, pre-assessment and staff training were organized, and a selected team of staff members received four mentoring sessions during one academic year.
Staff and students answer questionnaires at the end of school year 0, at post-intervention (year 1) and again at the 1-year follow-up (year 2). Our primary outcomes concern two main program components — universal and indicated actions — reflecting program fidelity. As secondary outcomes, we examine the level of bullying victimization and perpetration as well as students' perception of several program fidelity indicators. Finally, we assess several tertiary outcomes, collect resource data and conduct qualitative interviews to perform additional analyses.
Conclusion
This trial will inform us of whether implementation support can boost program fidelity and have a distal impact on bullying prevalence.